Determinants of Tax Non-Compliance in Budget-Friendly Boutique and Economy-Class Hotels in Nepal - Ojha, Gaurav (Nepalese Journal of Hospitality and Tourism Management, 2026)
This study examines tax non-compliance behavior among budgetfriendlyboutique and economy-class hotels in Nepal with reference toperceived fairness of the tax system, cost of tax compliance, coercivepower of tax authorities, complexity of the tax system, and peerinfluence and social norms. A quantitative cross-sectional researchdesign has been applied in this study to analyze the potential impactof these factors on the tax non-compliance behavior of these small,medium-sized, and economical hotels in Nepal. Data was collected fromemployees associated with 93 budget-friendly boutique and economyclasshotels located in Kathmandu, Lalitpur, Bhaktapur, Pokhara, andBharatpur. Here, N=187 owner/investors, hotel managers, and headsof accounts and finance departments participated in this study. Theresults indicate that the cost of tax compliance and peer influence/socialnorms are influential determinants of tax non-compliance behavioramong budget-friendly boutiques and economy-class hotels. Althoughcounterintuitive, this study challenges the conventional deterrencebasedassumption that coercive enforcement improves tax compliancebehavior. This study concludes that tax regulators need to implementpeer-based interventions and compliance-focused recognition programsand adopt supportive rather than punitive enforcement strategies fortax adherence among budget-friendly small- and medium-sized hotelsin Nepal.